Al-Gazālī’s Critique against the Muslim Philosophers in Tahāfut Al-Falāsifah - Qurratul Aini (Ulumuna, 2016)
This article discusses al-Gazālī’s critiques in his Tahāfut al-Falāsifah against the Muslim. It answers two main questions: First, what is the purpose of al-Gazālī in writing Tahāfut al-Falāsifah? Second, is it true that this work represent the conflict between philosophy and dogma, between revelation and the ratio, or between orthodoxy and hetherodoxy? Content analysis and historical method are used to elucidate the criticism of al-Gazālī against the Muslim philosophers in Tahāfut al-Falāsifah. This study shows that instead of questioning the validity of logic on philosophical reasoning and methodology, al-Gazālī wrote Tahāfut al-Falāsifah in order to contest epistemological philosophical superiority claims advanced by Muslim philosophers. The critism of al-Gazālī cannot be seen as a reaction, or let alone rejection, of orthodoxy or dogma against the philosophy. Rather, his critical thought should be viewed as his attempt as a Muslim scholar to accept and adapt Greek philosophical tradition into the framework of Islamic thought. DOI: http://dx.doi.org/10.20414/ujis.v20i1.805